African Human Rights Judicial System : streamlining structures and domestication mechanisms viewed from the foreign affairs power perspective. - Franceschi, Luis Gabriel (Newcastle upon Tyne : Cambridge Scholars Publishing, 2014)
This book deals with two interconnected yet often forgotten realities of the constitutional order in Africa: first, the 'foreign affairs power' that gives the specific organs of the State the capacity to create and empower universal, regional and sub-regional governance and judicial structures. Secondly, the 'international judicial function in Africa', with a specific focus on the African Court on Human and Peoples' Rights and the upcoming merger with the African Court of Justice to form one ...
Comprises of bibliographic references and an index
Keywords: Human Rights Africa (Organization); Human rights -- Africa; Droits de l'homme (Droit international) -- Afrique; Justice, Administration of -- Africa; International law and human rights; Droit international et droits de l'homme.; International law and human rights; Justice, Administration of; Africa